ANALYSIS PRIORITY OF THE USE OF VILLAGE FUNDS AND VILLAGE FUNDS ALLOCATION TO INCREASE THE VILLAGE DEVELOPMENT INDEX IN ENDE REGENCY - Ndonggi, Dionisius Hilarius; Putra, Fadillah; Nurani, Farida (Faculty of Administrative Science, Universitas Brawijaya, 2023)
Village funds and village fund allocations are the two main sources of income for village governments in Ende Regency. Priority use of village funds and allocation of village funds are intended for two main areas, namely village development and community empowerment. These two fields will be the main factors in seeing the development of village progress as measured through a measurement instrument called the village development index. In the period from 2017 to 2021, of course, many resources and development changes occurred in villages with the existence of village funds and allocation of village funds, whereas in the administrative area of Ende Regency, there are 255 villages spread across 19 districts. This research aims to conduct a priority analysis of the use of village funds and the allocation of village funds to increase the village development index in Ende Regency. This research uses quantitative methods with a panel data regression approach, and the data source used is secondary data consisting of village fund data, village fund allocation data, and village development index data for five years from 2017 to 2021 for a village population of 255 villages. The research results show that the village fund variable (DD) has a significant effect on the village development index (IDM), and the village fund allocation variable (ADD) does not have a significant effect on the village development index (IDM). Village government operations so that it does not have a significant effect on IDM